Patellar tendon ultrasonographic properties and lower limb function in rheumatoid arthritis patients - Samia Abd El Hamid Abd El Megid; Salwa Saeid El Gendy; Hussein Abd El Aziz Yassin; Marwa Mohamed Mohamed Ali Abd El Rahim; Mai Abd El Halim Abd El Razik Moussa (Egyptian Rheumatology and Rehabilitation, 2019)
Aim of work The aim of this work was to investigate patellar tendon (PT) biomechanical properties in rheumatoid arthritis (RA) patients through changes in ultrasonographic tendon properties and its effect on lower limb function. Patients and methods Forty RA patients and 20 healthy participants were included in this study. The physical function was assessed by Health Assessment Questionnaire, the activity of RA by disease activity score 28 and range of motion for all knees by a manual goniometer. RA patients were divided into the following groups: group I comprised patients with low disease activity score 28, who were further subdivided according to the presence of knee flexion deformity into two subgroups (GIA and GIB) and group II patients in the remission stage. Ultrasonography was used for measuring PT elongation and cross-sectional area and quadriceps’ muscle strength was measured. The lower limb function was assessed clinically by 50-foot walk test and smart balance master system through unilateral stance test, step up and over and sit to stand tests. Results There was an increased elongation of PT of all RA groups relative to the control group (P=0.001); no significant difference was found in the PT (cross-sectional area). RA patients showed quadriceps’ muscle strength reduction (P=0.001) and delayed walking time of the 50-foot walk test (P=0.05). Unilateral stance test showed increased center of gravity sway velocity during either eye open or eye closed conditions in RA groups and deterioration in all parameters of step up and over and sit to stand tests (P=0.05–0.001). All physical function evaluation of RA patients showed impairment associated with a reduction of PT stiffness and quadriceps’ strength. Conclusion Inflammation of the PT and peritendinous tissues in RA alters its biomechanical properties; this impairs RA patients’ physical and lower limb functions.